Karo Traditional Food Inventory in the Design of Culinary Branding in Karo - Zaitun; Enny Hasriyani; Ngatemin (Politeknik Pariwisata Medan, 2021)
This study has three research objectives,(1) Prepare a detailed inventory of traditional Karo foods which include: (a) Types of traditional foods (b) Traditional food processing methods, (c) Economic aspects and (d) Documentation, (2) Developing traditional food development alternatives and (3) designing Branding on traditional food in Karo District. The type of this research is survey research with descriptive method. The results Based on a survey conducted in Berastagi City identified a number of 5types of traditional food. The main ingredients most widely used for making traditional food is Chicken (80%), then other ingredients (20%). Karo traditional foods, based on the way of processing can be categorized into three, namely: (1) steamed, (2) fried, (3) and boiled. Based on interviews with resource persons and traditional food community figures in Karo, several alternative development that can be done are: Identification and Inventory of traditional food, Preparing the profile of traditional food in the area as food information and counseling and Promotion, Encouraging the development of traditional food centers with relevant agencies, private and community; Provision of soft loans for additional capital.